Synthesization of Low power Folded Tree Digital Signal Processor Architecture for WSN Applications - G. Kiran Kumar, Mr.; Shaik.Mahaboob Basha, Dr. (International Journal of Engineering and Technology, 2018)
To monitor the execution of Wireless Sensor Network (WSN) applications effectively, different parameters like pressure, viscosity etc., to be measured accurately. A unique WSN environment is to be established through radio communication. The main requirement for this is high energy consumed wireless network sensor nodes. This paper presents unique design of low power folded tree architecture for wireless network sensorâ€™s data processing through parallel prefix operations and data localization equipment.Â Â Â